Desentralisasi dalam Pengelolaan Air Irigasi Tersier (Suatu Studi dengan Kerangka Konsep Desentralisasi Teritorial dan Fungsional di Kabupaten dan Kota Tegal, Jawa Tengah, di Kabupaten Jembrana, Bali, dan di Hulu Langat, Selangor, Malaysia) - Maksum, Irfan Ridwan (UI Scholars Hub, 2006)
This research compared tertiary irrigation management in the Municipality and Regency of Tegal, the Regency of Jembrana, and the Regency of Hulu Langat Selangor Malaysia. Malaysia has been developing water board at National and State Level. Although the two countries differed in governmental arrangements, the locus used in this research experienced the same level of governments. Verstehen has been as a general framework of this research approach. Qualitative and descriptive were the method of this research. Data are gathered using eclectic-triangulation methods and analyzed with multilevel tools. This research concluded that the tertiary irrigation in those three locus in Indonesia were not established based on functional decentralization, eventhough it has potential to do so. It is different from Malaysia which is fully centralized through deconcentration. Only the teritorial decentralization is the basic of tertiary irrigation management in Indonesia. Functional decentralization is not being practiced in tertiary irrigation management both in Indonesia and Malaysia. Empirically, Government should improve the performance of irrigation organization at the grassroot level in order to increase the whole agricultural performance which creating special local regime in the irrigation management. Furthermore, amandment to the constitution of 18th article should induce the concept of functional decentralization that was practiced in Indonesian local government system in 1920.